2003
DOI: 10.4315/0362-028x-66.1.82
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm and Postharvest Processing Sources of Bacterial Contamination to Melon Rinds

Abstract: Multistate and international foodborne illness outbreaks, particularly involving cantaloupe and often involving rare Salmonella spp., have increased dramatically over the past 13 years. This study assessed the sources and extent of melon rind contamination in production fields and at processing and packing facilities. In the spring of 1999, cantaloupe (Cucumis melo L. [reticulatus group] cv. Cruiser) sampled from two sites in the Rio Grande River Valley showed that postharvest-processed melon rinds often had g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 18 publications
1
63
0
Order By: Relevance
“…These findings are consistent with findings of previous studies (14,25,26,47,51,52) that identified irrigation water as a potential preharvest source of bacterial contamination of produce. Multiple studies have also reported significant associations between irrigation water and fresh produce contamination (12,13,19,20). The relationship between irrigation and L. monocytogenes isolation in this study may be explained by the fact that surface water is a known reservoir of foodborne pathogens in produce production environments (22,(52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These findings are consistent with findings of previous studies (14,25,26,47,51,52) that identified irrigation water as a potential preharvest source of bacterial contamination of produce. Multiple studies have also reported significant associations between irrigation water and fresh produce contamination (12,13,19,20). The relationship between irrigation and L. monocytogenes isolation in this study may be explained by the fact that surface water is a known reservoir of foodborne pathogens in produce production environments (22,(52)(53)(54)(55)(56).…”
Section: Discussionmentioning
confidence: 65%
“…Although most listeriosis outbreaks associated with fresh produce are traced back to processing environments, the prevention of produce contamination in production environments is crucial. In fact, previous studies have shown that low-level sporadic contamination of produce in production environments can result in pathogen proliferation and widespread contamination throughout the supply chain (11)(12)(13). In order to minimize preharvest produce contamination, it is necessary to understand how different spatial (e.g., proximity to water and roads) and temporal (e.g., time since irrigation) factors affect the likelihood of a contamination event in production environments.…”
mentioning
confidence: 99%
“…The available literature, however, highlights contaminated irrigation water sources or insufficiently disinfected process water as the most probable sources for contamination during melon and watermelon production (Gagliardi et al, 2003;Castillo et al, 2004;McCallum et al, 2010). Amongst the Salmonella outbreaks associated with melon consumption, risk factors at pre-harvest were identified with contaminated soil, manure, irrigation water, water used in pesticide application and animals (rodents, birds, insects or reptiles) in the production area (Bowen et al, 2006).…”
Section: Risk Factors For Microbiological Contamination During Agricumentioning
confidence: 99%
“…There is more limited information on a restricted range of Salmonella serovars available for adherence to the surface of melon and watermelon types other than cantaloupe (Gagliardi et al, 2003;Parnell et al, 2005).…”
Section: Factors Linked To the Adherence Survival And Internalisatiomentioning
confidence: 99%
“…This approach also mimics certain aspects of the cross-contamination process in which contaminated water may be sprayed on fresh produce during vacuum cooling. Sanitation of the processing water used during cooling and washing has been a subject of significant concern in the fresh produce-processing industry (19)(20)(21). In order to determine the average load sprayed onto the leaf disks, leaf disks with surface-inoculated E. coli O157:H7 GFPlux were prepared and vortexed in 5 ml of 1ϫ PBS buffer for 10 min immediately following inoculation.…”
Section: Methodsmentioning
confidence: 99%